Fast infrared variability from the black hole candidate MAXI J1535−571 and tight constraints on the modelling. Issue 1 (19th February 2021) - Vincentelli, F M; Casella, P; Russell, D M; Baglio, M C; Veledina, A; Maccarone, T; Malzac, J; Fender, R; O'Brien, K; Uttley, P
ABSTRACT: We present the results regarding the analysis of the fast X-ray/infrared (IR) variability of the black hole transient MAXI J1535−571. The data studied in this work consist of two strictly simultaneous observations performed with XMM–Newton (X-rays: 0.7–10 keV), VLT/HAWK-I ( K s band, 2.2 μm) and VLT/VISIR ( M and PAH 2_2 bands, 4.85 and 11.88 μm, respectively). The cross-correlation function between the X-ray and near-IR light curves shows a strong asymmetric anticorrelation dip at positive lags. We detect a near-IR QPO (2.5 σ ) at 2.07 ± 0.09 Hz simultaneously with an X-ray QPO at approximately the same frequency ( f 0 = 2.25 ± 0.05). From the cross-spectral analysis, a lag consistent with zero was measured between the two oscillations. We also measure a significant correlation between the average near-IR and mid-IR fluxes during the second night, but find no correlation on short time-scales. We discuss these results in terms of the two main scenarios for fast IR variability (hot inflow and jet powered by internal shocks). In both cases, our preliminary modelling suggests the presence of a misalignment between the disc and jet.